Pengembangan Media Pembelajaran Berbasis Komputer pada Pokok Bahasan Himpunan Guna Meningkatkan Pemahaman Mahasiswa - Eka Setyaningsih; Hindayati Mustafidah (JUITA : Jurnal Informatika, 2010)
This Research is depended on the students study results are lower in Set Subject, those are caused by their small knowledge level.  In this research is conducted to develop interactive computer base learning media especially in set topic. The goal of this learning media development is to assist the student in comprehending in set topic, because this media provides some interactive menus that facilitate the students to use it.  This research uses literature study method about how to compile the computer base learning media and set topic. The stages of this research are analyzing set books, designing the model of computer base learning media, and compiling the computer program. Result of this research is a learning media in the form of interactive computer program which can be used by students as an assist tool to learn the set topic. This media is consisted of two main parts, they are theory and problem practice. At the theory part, students can learn the theory of set, while at problem practice part students can exercise to do the practice problem about set. At this part is also provided with scoring, that is if answer given by real correct student, hence media will give the score and correct signal. This matter can be used to know whether students have mastered the set topic or not yet. Thereby, it is expected a student will continue to exercise the practice problem till reaches the optimum understanding level.